SEASONAL EARTH TIDE VARIATIONS AS A MODEL OF EARTHQUAKE PRECURSOR - Latynina L.A.; Boyarskii E.A. (My University, 2000)
This paper is concerned with seasonal variations in Earth tidal strain amplitudes as recorded at the Protvino station. These variations are much too large to be daily variations and seem to be caused by meteorological factors. The disturbance of the lunar wave M2 consists of a meteorological and an elastic component. The latter, about 10% in magnitude, is caused by seasonal variations in the physical properties of the rocks resulting from changes in their water content. Seasonal variations in the rock properties can be used to model the processes operating in the precursory zones of earthquakes and for evaluating the expected Earth tide precursors.